A Study on Nutritional Status of Rural School going Children in Kavre District - Mansur, D.I.; Haque, M.K.; Sharma, K.; Mehta, D.K.; Shakya, R. (Kathmandu University Medical Journal, 2017)
Background Childhood is a time of active growth in terms of physical size, mental, emotional and psychological development. Normal growth is dependent on adequate nutrition and encompasses major transformations from birth to adulthood. Nutrition is a focal point for health and well being; and has special significance in countries with disadvantages in socioeconomic and hygienic standards. Objective The objective of the present study was to assess the nutritional status in terms of prevalence of underweight, stunting and thinness among rural school going children. Method The present study was cross-sectional study, conducted on 438 rural school going children (169 male and 259 female) with the age group 4-16 years, during the period from April 2014 to July 2014. Age was recorded in year; height and weight were measured in centimeter and kilogram respectively. BMI was calculated by using standard equation. Result The present study concluded that the nutritional status in terms of prevalence of underweight, stunting and thinness were found to be 30.85%, 24.54% and 10.05% respectively among rural school going children of Kavre district. It was revealed that 37.87% was underweight, 29.59% was stunted and 11.25% was thinness among male children whereas in female children, 26.27% was underweight, 21.24% was stunted and 9.27% was thinness. Hence, high prevalence of underweight, stunting and thinness were observed in male than in female children. Conclusion The present study has successfully documented the nutritional status in terms of prevalence of underweight, stunting and thinness among the rural school going children of Kavre district. The results of the present study will be useful for policy makers in their endeavor to formulate various developmental and health care programs.